1987
DOI: 10.1111/j.2044-8325.1987.tb00236.x
|View full text |Cite
|
Sign up to set email alerts
|

Managerial motivation among MBA students: A longitudinal assessment

Abstract: A longitudinal study of the effects of business school training on the motivation to manage of Masters of Business Administration (MBA) students was conducted using the forced‐choice version of the Miner Sentence Completion Scale (MSCS). Male MBA students had significantly higher levels of motivation to manage than female MBA students, with part‐time females registering the lowest managerial motivation levels among the MBA students. Managerial motivation scores were significant predictors of salary after gradu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

1987
1987
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 12 publications
0
6
0
1
Order By: Relevance
“…Ten spyte van hierdie ondersteunende bevindings is daar ook heelwal kriliek tee n hierdie meet instrument gcapper (Overstreet, 1980; Bartol, Schneier en Anderson, 1985; Miner et aI., 1985; Stahl, 1986). Sommige navorsers beweer dal daar 'n moontlikheid van syd igheid ten opsigte van geslag in die MSCS bestaan (Barlol, Anderson en Schneier, 1980; Bartol en Martin, 1987). Ander navorsers wys weer daarop dat die MSCS sen-7 siliE'f mag wees vir kulturele verskille en dal sekere ilemslamme verouderd mag wees (Overstreet, 1980).…”
unclassified
“…Ten spyte van hierdie ondersteunende bevindings is daar ook heelwal kriliek tee n hierdie meet instrument gcapper (Overstreet, 1980; Bartol, Schneier en Anderson, 1985; Miner et aI., 1985; Stahl, 1986). Sommige navorsers beweer dal daar 'n moontlikheid van syd igheid ten opsigte van geslag in die MSCS bestaan (Barlol, Anderson en Schneier, 1980; Bartol en Martin, 1987). Ander navorsers wys weer daarop dat die MSCS sen-7 siliE'f mag wees vir kulturele verskille en dal sekere ilemslamme verouderd mag wees (Overstreet, 1980).…”
unclassified
“…c) Women may lack motivation. A recent study of managerial motivation among 232 MBA students at a large Eastern state university in the United States indicated that "male MBA students had significantly higher levels of motivation to manage than female MBA students, with part-time females registering the lowest managerial motivation" (Bartol et al, 1987). Further the study could find "no significant difference in management motivation levels associated with business school MBA training".…”
Section: Sex Differences In the Home Employment Marketmentioning
confidence: 76%
“…Findings of empirical researches from Allan and Nellen (1992), Bartol and Martin (1987), and Bartol et al (1981) prove that women motivation to lead is lower than men. These three researches are conducted in America that is known with its western culture.…”
Section: Lite Rature Reviewmentioning
confidence: 99%